CURRENT STATUS OF ICTHYOFAUNAL DIVERSITY OF TUNGA RIVER AT MANDAGADDE BIRD SANTUARY, SHIVAMOGGA, KARNATAKA, INDIA - SAYESWARA HA (Innovare Journal of Sciences, 2017)
ABSTRACT Objective: The objective of this study was to find out the diversity of fishes of Tunga river at Mandagadde bird sanctuary. Methods: The fishes were collected with the help of fisherman by repeated netting from selected localities during the study period from April to October 2016.Â  Fishes were photographed at first for documentation of the fresh color and then preserved in 10% formalin. Systematic identification of fish species were carried out by using the standard keys. Results: A total of 16 species of fishes belonging to 4 orders, 8 families and 12 genera were recorded from the study area. Six species sighted in family Cyprinidae. Channidae, Cichlidae and Siluridae were represented by two species each. Families Bagridae, Heteropneustidae, Notopteridae and Schilbeidae had only a single species each. Conclusion: This study highlights the rich concentration of fish species, economically important and of high commercial value. Keywords: Icthyofauna, Mandagadde bird sanctuary, Conservation status, Shivamogga, Karnataka